2019
DOI: 10.1080/15384101.2018.1560205
|View full text |Cite
|
Sign up to set email alerts
|

Ras signals principally via Erk in G1 but cooperates with PI3K/Akt for Cyclin D induction and S-phase entry

Abstract: Numerous studies exploring oncogenic Ras or manipulating physiological Ras signalling have established an irrefutable role for Ras as driver of cell cycle progression. Despite this wealth of information the precise signalling timeline and effectors engaged by Ras, particularly during G1, remain obscure as approaches for Ras inhibition are slow-acting and ill-suited for charting discrete Ras signalling episodes along the cell cycle. We have developed an approach based on the inducible recruitment of a Ras-GAP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…The antiproliferative effects of TRPML1-inhibition results from an increase in the fraction of cells in the G 0 /G 1 phase of the cell cycle and corresponding decreases in the fractions of cells in S and G2/M phases. These data agree with G 1 arrest being an outcome of MEK-ERK inhibition in RAS-transformed cancer cells (Chambard et al, 2007;Vasjari et al, 2019;Yamamoto et al, 2006). Because ML-SI1 slowed the progression of cancer cells through the cell cycle rather than inducing cell death, simultaneous application of the drug with the cytotoxic agent, cisplatin, led to a purely additive decline of T24 cell number.…”
Section: Trpml1 Supports Oncogene-induced Proliferation In P53-deficient Bladder Cancer Cellssupporting
confidence: 80%
“…The antiproliferative effects of TRPML1-inhibition results from an increase in the fraction of cells in the G 0 /G 1 phase of the cell cycle and corresponding decreases in the fractions of cells in S and G2/M phases. These data agree with G 1 arrest being an outcome of MEK-ERK inhibition in RAS-transformed cancer cells (Chambard et al, 2007;Vasjari et al, 2019;Yamamoto et al, 2006). Because ML-SI1 slowed the progression of cancer cells through the cell cycle rather than inducing cell death, simultaneous application of the drug with the cytotoxic agent, cisplatin, led to a purely additive decline of T24 cell number.…”
Section: Trpml1 Supports Oncogene-induced Proliferation In P53-deficient Bladder Cancer Cellssupporting
confidence: 80%
“…For example, the RAS-MAPK’s ERK1/2 end kinase is known to regulate the transcription of several hundred genes through its activation of a vast array of transcription factors. Through ERK1/2 regulation of transcription, RAS-MAPK regulates the progression of cells from the G1 to the S phase by activating expression of Cyclin D [ 48 , 49 ]. Interestingly, Cyclin D1 is also a well-established NB oncogene that is associated with 11q13.3 gains [ 50 ].…”
Section: Biology Of the Ras-mapk Pathwaymentioning
confidence: 99%
“…The effect TRPML1 inhibition on T24 proliferation was associated with an increased fraction of cells in the G 0 /G 1 phase of the cell cycle, and a corresponding decrease in the fraction of cells in Sand G2/M-phases. Since G 1 arrest is an outcome of MEK-ERK inhibition in RAS transformed cancer cells (Chambard et al, 2007;Vasjari et al, 2019;Yamamoto et al, 2006), the role for TRPML1 in HRAS G12V -ERK signaling that we demonstrated previously explains the phase of the cell cycle that is sensitive to TRPML1 inhibition. Notably, since ML-SI1 slowed progression through the cell cycle, the drug did not synergize with the cytotoxic agent, cisplatin.…”
Section: Trpml1 Supports Oncogene-induced Proliferation In P53-deficimentioning
confidence: 51%